2014
DOI: 10.1017/s0022215114002813
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effectiveness of nasal dilator strips: does race play a role?

Abstract: Nasal peak inspiratory flow, minimum cross-sectional area and visual analogue scale values improved from baseline with strip application in both populations. Only Caucasians experienced significant nasal airway resistance improvement with strip application. Both cohorts experienced nasal peak inspiratory flow improvement, with Caucasians experiencing a significantly larger improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…15 For example, it has been shown that nasal dilator strips may have varied impact on peak inspiratory flow between population groups, with efficacy affected by thickness of the skin envelope. 16 Placement of the butterfly cartilage graft directly onto the ULCs will apply the greatest expansile force possible, and will also minimize the effect of the dorsal skin and soft tissue variable. 16 Additionally, from an aesthetic perspective, given the thicker SSTE seen in non-Caucasian patients, the BFG is well camouflaged in the mid vault.…”
Section: Ethnic Rhinoplasty Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 For example, it has been shown that nasal dilator strips may have varied impact on peak inspiratory flow between population groups, with efficacy affected by thickness of the skin envelope. 16 Placement of the butterfly cartilage graft directly onto the ULCs will apply the greatest expansile force possible, and will also minimize the effect of the dorsal skin and soft tissue variable. 16 Additionally, from an aesthetic perspective, given the thicker SSTE seen in non-Caucasian patients, the BFG is well camouflaged in the mid vault.…”
Section: Ethnic Rhinoplasty Considerationsmentioning
confidence: 99%
“…16 Placement of the butterfly cartilage graft directly onto the ULCs will apply the greatest expansile force possible, and will also minimize the effect of the dorsal skin and soft tissue variable. 16 Additionally, from an aesthetic perspective, given the thicker SSTE seen in non-Caucasian patients, the BFG is well camouflaged in the mid vault.…”
Section: Ethnic Rhinoplasty Considerationsmentioning
confidence: 99%
“…In addition to classical surgical procedures for the improvement of nasal breathing, further therapeutic options exist, particularly for the treatment of too narrow nasal valves, including minimally invasive procedures on the one hand and widening nasal strips on the other hand [89], [90], [91], [92]. However, for both therapeutic options, there are very few scientific publications.…”
Section: Types and Therapies Of Nasal Obstructionmentioning
confidence: 99%
“…Neben den klassischen chirurgischen Verfahren zur Verbesserung der Nasenatmung existieren insbesondere für die Behandlung einer engen oder zu engen Nasenklappe weitere Therapieoptionen, wie einerseits minimalinvasive chirurgische Verfahren und andererseits erweiternde Nasenpflaster [88][89][90][91]. Für beide Therapieoptionen existieren jedoch nur wenige wissenschaftliche Publikationen.…”
Section: Evidenz Nicht-chirurgischer Und Nichtmedikamentöser Therapieunclassified